2015
DOI: 10.1097/inf.0000000000000483
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Vitamin D3 Supplementation in Children and Young Adults with HIV

Abstract: Background Suboptimal vitamin D status is prevalent in HIV-infected patients and associated with increased risk of disease severity and morbidity. We aimed to determine 12-mo safety and efficacy of daily 7000IU vitamin D3 (vitD3) vs placebo to sustain increased serum 25-hydroxyvitamin D (25(OH)D) and improve immune status in HIV-infected subjects. Methods This was a double-blind trial of perinatally- (PHIV) or behaviorally-acquired (BHIV) HIV-infected subjects (5.0–24.9y). Safety, 25(OH)D-related parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 61 publications
1
57
0
5
Order By: Relevance
“…Few randomized, placebo-controlled trials of vitamin D supplementation have been conducted in HIV-infected children and adolescents 2428 , and only two studies to date have evaluated bone changes with supplementation 24,27 . In Eckard, et al , authors investigated changes in BMD after 12 months of supplementation in 102 HIV-infected youth 8–26 years old on ART with baseline 25(OH)D ≤30 ng/mL 27 .…”
Section: Role Of Vitamin D Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Few randomized, placebo-controlled trials of vitamin D supplementation have been conducted in HIV-infected children and adolescents 2428 , and only two studies to date have evaluated bone changes with supplementation 24,27 . In Eckard, et al , authors investigated changes in BMD after 12 months of supplementation in 102 HIV-infected youth 8–26 years old on ART with baseline 25(OH)D ≤30 ng/mL 27 .…”
Section: Role Of Vitamin D Deficiencymentioning
confidence: 99%
“…Another recent study performed on a cohort of 58 HIV-infected youths assessed the effect of a daily high-dose supplementation with 7,000 IU of vitamin D 28 . An interesting finding was related to the unchanged parathyroid hormone (PTH) concentration observed despite the increase in 25(OH)D. The majority of subjects were vitamin D deficient at baseline, so one would have expected a decrease in PTH with vitamin D supplementation which was not the case.…”
Section: Role Of Vitamin D Deficiencymentioning
confidence: 99%
“…1 In a randomized trial of 58 HIV-infected children and young adults, we showed that those supplemented with daily 7000-IU vitD 3, compared with placebo, had not only increased 25(OH)D but also an improved HIV immune profile. 2 Over the 12-month follow-up, 25(OH)D was maintained at an average of 29.8 ± 1.9 ng/mL (least squares mean ± SE) with supplementation, compared with 17.7 ± 2.0 ng/mL for the placebo group (P < .001). The percentage of naïve T-helper cells were significantly increased; T-helper cells marginally increased with supplementation in those taking combination antiretroviral therapy (cART); and there was a significantly reduced RNA viral load.…”
Section: Introductionmentioning
confidence: 92%
“…In this trial, the vitamin D concentrations were higher in the intervention group for most of the study duration but were not different at the last measurement that was four months after the last dose. Also, whether the intermittent bolus therapy of vitamin D as used in this trial may be more efficient than a regimen of daily therapy in increasing serum vitamin D concentrations is still uncertain as the evidence is mixed (Emel 2012; Tan 2015). In conclusion, there appears to be no benefit of vitamin D with regard to preventing infections, that is pneumonia and diarrhoea.…”
Section: Authors' Conclusionmentioning
confidence: 99%